On-farm green water estimates as a tool for increased food production in water scarce regions - Rockstroem, J (Physics and chemistry of the earth. Part B, Hydrology, oceans and atmosphere, 1999)
Rainfed agriculture covers > 95 % of the crop lands in water scarce tropical regions, and will in a forseeable future be the dominating source of food for growing populations in the tropics. Despite this fact, focus has until recently been on water used for irrigated agriculture, industry and households--the so called ``blue'' water recharging rivers, lakes and aquifers. Yield levels have to increase substantially in order to guarantee a minimum of livelihood security in dry tropical regions. This paper focuses on the potential of improving the efficient use of rainfall through integrated soil nutrient and water management. Results are presented from an on-farm water balance research project on pearl millet in the Sahel (Niger). The findings indicate that only a very small fraction of the rainfall, 4-9%, takes the productive water flow path as ``green'' transpiration water. Surface runoff was substantial, amounting to 25-50 % of rainfall for intensive events, despite sandy soils. Soil evaporation amounted to around 50% of annual rainfall. Drainage was significant in this dryland farming system, despite the presence of periods of severe water scarcity during critical growth phases. Very low water use efficiencies were observed, with a range of 4000-8000 m super(3) of evapotranspiration water needed to produce 1 ton of grain yield, indicating a large potential for increased yield and productive ``green'' water flow. An option discussed is water harvesting techniques for supplementary irrigation.